Folklore - Ahamada, Oyakila, 1941-; Asiatic Society of Bangladesh; Cultural Survey of Bangladesh Project (Dhaka : Asiatic Society of Bangladesh, 2007)
Contributed articles published under the Cultural Survey of Bangladesh Project.
00026334
Includes translations from Bengali.
Includes bibliographical references and index.
Keywords: Folklore -- Bangladesh